Flavor from the electroweak scale - Bauer, Martin; Carena, Marcela; Gemmler, Katrin M. (Journal of high energy physics, 2015)
We discuss the possibility that flavor hierarchies arise from the electroweak scale in a two Higgs doublet model, in which the two Higgs doublets jointly act as the flavon. Quark masses and mixing angles are explained by effective Yukawa couplings, generated by higher dimensional operators involving quarks and Higgs doublets. Modified Higgs couplings yield important effects on the production cross sections and decay rates of the light Standard Model like Higgs. In addition, flavor changing neutral currents arise at tree-level and lead to strong constraints from meson-antimeson mixing. Remarkably, flavor constraints turn out to prefer a region in parameter space that is in excellent agreement with the one preferred by recent Higgs precision measurements at the Large Hadron Collider (LHC). Direct searches for extra scalars at the LHC lead to further constraints. Precise predictions for the production and decay modes of the additional Higgs bosons are derived, and we present benchmark scenarios for searches at the LHC Run II. Flavor breaking at the electroweak scale as well as strong coupling effects demand a UV completion at the scale of a few TeV, possibly within the reach of the LHC.
Gesehen am 10.01.2018